Battery asset management with cycle life prognosis. (December 2021) - Liu, Xinyang; Zheng, Zhuoyuan; Büyüktahtakın, İ. Esra and Zhou, Zhi and Wang, Pingfeng
Highlights: Integrate battery cycle life prognosis with parallel asset management. Present a mathematical model for the battery asset replacement problem. Reduce lifecycle cost of the battery energy storage system. Develop an asset replacement planning method to minimize cost. Demonstrate the methodology with case study and result analysis. Abstract: Battery Asset Management problem determines the minimum cost replacement schedules for each individual asset in a group of battery assets that operate in parallel. Battery cycle life varies under different operating conditions including temperature, depth of discharge ( DOD ), charge rate, etc., and a battery deteriorates due to usage, which cannot be handled by current asset management models. This paper presents a new battery asset management methodology where battery cycle life prognosis is integrated with parallel asset management to reduce lifecycle cost of the Battery Energy Storage Systems (BESS). For the battery failure time prognosis, a nonlinear physics-based battery capacity fade model is developed and incorporated in parallel asset management model to update battery capacity over time. Experiment results have shown that the developed battery asset management methodology can be conveniently used to facilitate BESS asset management decision making thereby decreasing asset lifecycle costs.